2006
DOI: 10.1037/1089-2699.10.2.136
|View full text |Cite
|
Sign up to set email alerts
|

Measuring group processes: A comparison of the GCQ and CCI.

Abstract: This study verified and compared the factor structures of two frequently used measures of small group climate, the Group Climate Questionnaire (GCQ-S; MacKenzie, 1983) and the Curative Climate Instrument (CCI; Fuhriman, Drescher, Hanson, Henrie, & Rybicki, 1986) at both group and individual levels. Data included third session assessments of 124 group members in 20 university counseling center groups. Confirmatory factor analyses partially supported the GCQ factor structure, but indicated that the Catharsis sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 17 publications
(33 reference statements)
3
75
0
Order By: Relevance
“…Cronbach Alpha levels ranged from .87-.93 for cohesion, .81-.87 for catharsis, and .79-.84 for insight (8,40). However, later studies reported lower reliability figures; .79 for cohesion, .70 for catharsis, and .34 for insight (26).…”
Section: Psychometric Properties Of the CCImentioning
confidence: 94%
See 4 more Smart Citations
“…Cronbach Alpha levels ranged from .87-.93 for cohesion, .81-.87 for catharsis, and .79-.84 for insight (8,40). However, later studies reported lower reliability figures; .79 for cohesion, .70 for catharsis, and .34 for insight (26).…”
Section: Psychometric Properties Of the CCImentioning
confidence: 94%
“…The CCI measures usefulness of therapeutic factors in group psychotherapy (40). The CCI consists of 14 items and 3 subscales: Catharsis, Cohesion, and Insight.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations